DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA DI WILAYAH PUSKESMAS KENTEN PALEMBANG TAHUN 2021 - Italia; Yuni Anika (Jurnal Kesehatan dan Pembangunan, 2023)
Old age is an event that will definitely be experienced by everyone who is blessed with a long life, its occurrence cannot be avoided by anyone, but humans can try to prevent its occurrence. According to the World Health Organization (WHO) in 2050, the Southeast Asian region aged over 60 years will number 142 million people and it is estimated that this will increase by 3 times. The purpose of this study was to determine family support for the quality of life of the elderly in the Kenten Palembang Health Center area. The research method uses qualitative descriptive. In this study, the sample consisted of 6 people consisting of 3 elderly people and 3 family members. The sampling technique used purposive sampling method. The results obtained from interviews with the three informants it is known that the three informants are well taken care of by their families by meeting all the needs of the elderly. This is in accordance with the answers of key informants who stated that the family had fulfilled all the needs of the elderly and cared for the elderly with love. Suggestions are expected that the family can always provide support to the elderly by meeting all the daily needs of the elderly and always paying attention to the health conditions of the elderly so that they can improve the quality of life of the elderly.Dukungan Keluarga, Kualitas Hidup, Lansia